Vascular alterations in apolipoprotein A-I amyloidosis (Leu75Pro). A case–control study. (September 2015) - Muiesan, Maria Lorenza; Salvetti, Massimo; Paini, Anna; Agabiti Rosei, Claudia; Rubagotti, Giulia; Negrinelli, Alessandro; Gregorini, Gina; Cancarini, Giovanni; Calabresi, Laura; Franceschini, Guido; Obici, Laura; Perlini, Stefano; et al.
Abstract Background: Among hereditary amyloidoses, apolipoprotein A-I (APO A-I) amyloidosis (Leu75Pro) is a rare, autosomal dominant condition in which renal, hepatic, and testicular involvement has been demonstrated. Objective: To investigate vascular structural as well as functional alterations. Methods: In 131 carriers of the amyloidogenic Leu75Pro APO A-I mutation (mean age 52 + 16 years, 56 women) and in 131 subjects matched for age, sex, body mass index and clinic blood pressure (BP), arterial stiffness (pulse wave velocity, PWV) and carotid intima-media thickness (IMT) were measured. Results: By definition no differences for age, sex, body mass index, and BP were observed. Meanmax IMT (Mmax–IMT) in the common (CC), bifurcation (BIF) and internal (ICA) carotid artery were comparable in the two groups. After adjustment for high-density lipoprotein cholesterol and renal function differences between the two groups, a lower meanmax–IMT was observed in APO A-I Leu75Pro mutation carriers than in controls (CC Mmax–IMT 0.87 ± 0.21 versus 0.93 ± 0.2 mm, p = 0.07; BIF Mmax–IMT 1.19 ± 0.48 versus 1.36 ± 0.46 mm, p = 0.025; ICA Mmax–IMT 0.9 ± 0.37 versus 1.02 ± 0.35 mm, p = 0.028). On the other hand, aortic stiffness was significantly greater in patients with APO A-I amyloidosis than controls (PWV 11.5 ± 2.9 and 10.7 ± 2.3 m/s, p < 0.05), even after adjusting for confounders. Conclusions: In carriers of the amyloidogenic Leu75Pro APO A-I mutation, a significant increase in arterial stiffness is observed; on the contrary, carotid artery IMT is comparable to that of control subjects. These results may add significant information to the clinical features of this rare genetic disorder.